Annual dynamics of the UHI phenomenon in a small urban system - Pipenbaher, Nataša; Ivajnšič, Danijel; Žiberna, Igor; Donša, Daša; Kaligarič, Mitja; Škornik, Sonja; Kajfež Bogataj, Lučka; Črepinšek, Zalika; Grujić, Veno Jaša (Journal for Geography, 2020)
The urban heat island phenomenon (UHI) is a consequence of anthropogenic activity and local climatic conditions. Most UHI studies address large metropolitan areas. However, the data show that UHI magnitude can reach high values even in small urban systems. The study focused on the seasonal dynamics of the UHI magnitude variable (average, maximum and minimum temperature anomaly) in the town of Ljutomer by considering different weather types. Under anticyclonic or advective air circulation pattern, predominantly in summer, UHI magnitude in Ljutomer can reach values comparable to midsize or large urban systems (up to 8°C). The results of such studies are of particular concern in regard to increasing frequency of heat waves as a consequence of climate change, which further increases the already present heat stress in cities all over the Globe.